Investigation of the tool wear behaviour in shear-clinching processes during the running-in phase - Wiesenmayer, Sebastian; Han, Daxin; Meschut, Gerson; Merklein, Marion (AIP Conference Proceedings, 2019)
The multi-material design of modern cars is a challenge for common joining technologies. Joining by welding is often not possible, due to different melting temperatures of the joining partners. Indeed, the usage of fasteners allows the joining by forming of high-strength steels with aluminium, but increases the weight and the costs. Common joining by forming technologies without additional fasteners are limited by the mechanical properties of the joining partners. Thus, clinching of ultra-high strength steels with low ductility, like press-hardened manganese-boron steels, is not possible. However, the innovative shear-clinching technology enables the joining by forming of ultra-high strength steels and aluminium without fasteners. In one combined process, the die-sided steel sheet is cut and the punch-sided aluminium is pressed into the cut out hole, resulting in a form and force fitting joint. Nevertheless, the cutting of the high-strength steel and the subsequent upsetting of the aluminium both lead to high tool loads, especially for the die. Thus, it is necessary to analyse the wear behaviour of the shear-clinching tool. Within the scope of this work, the tool wear behaviour in shear-clinching and the influence of wear on the process will be investigated experimentally. The focus will be on the die and the running-in phase, since there are no references for the wear behaviour in shear-clinching yet.
CRIS-Team Scopus Importer:2019-07-23